Vacancy-controlled friction on 2D materials: Roughness, flexibility, and chemical reactions. (February 2019) - Liu, Jun; Qi, Yizhou; Li, Qunyang; Duan, Tianying; Yue, Wen; Vadakkepatt, Ajay; Ye, Chang; Dong, Yalin
Abstract: It was recently reported that the presence of vacancy could dramatically increase nanoscale friction of graphene, while its underlying mechanism remains unknown [1]. In this study, molecular dynamics simulation is carried out to examine the possible mechanisms that could contribute to friction enhancement on chemically modified and/or vacancy-contained graphene. It is found that the change in out-of-plane flexibility due to vacancies has only a limited influence on friction. In contrast, the Schwoebel barrier, the chemical reactivity of dangling bonds at the atomic step edges, as well as the roughening induced by functional groups can contribute more to nanoscale friction of graphene. This study provides a friction-mechanism map that correlates frictional behavior to various atomic scale mechanisms, which is useful for understanding the nanoscale friction of defected graphene. Graphical abstract: Image 1